Mystery of crop circles - Oxlade, Chris (Chicago : Heinemann Library, 2001)
Describes the appearance of the phenomena known as crop circles and offers various explanations as to how they were created.
Includes bibliographical references (p. 31) and index.
Keywords: Science -- Miscellanea -- Juvenile literature; Crop circles -- Miscellanea -- Juvenile literature; Curiosities and wonders -- Miscellanea -- Juvenile literature; Crop circles